Effect of YjbK, a CYTH-like Protein, on the Biosynthesis of Cereulide in Foodborne Bacillus cereus - LIANG Xinmin, LI Jiaxun, LI Yangfu, QIN Keyuan, LI Xiang, ZHANG Jumei, WANG Juan, WU Qingping, DING Yu (Shipin Kexue)
Our aim was to explore the synthesis mechanism of cereulide in Bacillus cereus, causing vomiting-type food poisoning. In this study, the potential regulatory gene yjbK was knocked out by homologous recombination, revealing that yjbK positively regulated the synthesis of cereulide in B. cereus. Through bioinformatics analysis, the potential phosphohydrolase activity of YjbK and the key sites of ExExK were determined. Subsequently, point mutant expression and complementary strains of YjbK were constructed, and it was clarified that mutations at sites E6 and E8 significantly reduced the activity of phosphohydrolase and the yield of cereulide, thereby confirming that phosphohydrolase activity positively regulated the synthesis of cereulide in B. cereus. This study provides a new theoretical basis for understanding the molecular regulatory mechanism of cereulide synthesis.